Chlorate as an inorganic disinfection by product in swimming pools = Chlorat als anorganisches Desinfektionsnebenprodukt in Schwimmbeckenwasser - Erdinger, Lothar; Kirsch, Frank; Sonntag, Hans-Günther (Zentralblatt für Hygiene und Umweltmedizin, 1999)
Chlorate and chlorite concentrations were determined in water samples taken from 33 swimming pools. In the pools under investigation, disinfection of the water is carried out either by gaseous chlorine (n = 14) or hypochlorite solution in conjunction with flocculation and sand filtration. A number of the pools also use ozone treatment to augment the disinfection process. Chlorite was not detectable in any of the samples (detection limit 1 mg/l). High concentrations of chlorate were detected in samples from a number of the pools; in one case as high as 40 mg/l. Higher chlorate concentrations were found to be associated with those pools using hypochlorite solution as a disinfecting agent. In contrast, relatively low chlorate concentrations were found in pools treated with gaseous chlorine. In order to elucidate any relationship between the chlorate content of pool water and that of the respective hypochlorite stock solution, chlorate and bromate concentrations were determined in the hypochlorite stock solutions of nine pools. Bromate concentration in the stock solutions were not found to exceed 1.2 g/l, chlorate was measured in concentrations of up to 44.5 g/l. The additional use of ozone as part of the water purification process appears to have no significant influence on chlorate concentration. Chlorate has no bactericidal properties and does not interfere with the measurement of certain parameters relevant to hygiene in swimming pools such as free and combined chlorine, pH or redox potential. At present, the effects of high chlorate concentrations in swimming pool water are unclear. Our initial investigations indicate that chlorate has no cytotoxic (Neutral-Red assay) or irritating properties (HET-CAM assay). However, both chlorate and chlorite are known to interfere with the haematopoetic system. In Germany, the MCL for chlorite in drinking water is 0.2 mg/l. It is therefore strongly recommended that measures should be taken to reduce chlorate concentrations in swimming pool water. Zusammenfassung: Im Rahmen dieser Studie wurde der Chlorit- und Chloratgehalt von 33 Schwimmbädern untersucht, deren Wasser mit Chlorgas (n = 14), bzw. mit Hyperchlorit-Lösung desinfiziert wird. In einigen der Bäder wird zusätzlich zu Flockung and Sandfiltration eine Ozonstufe für die Wasseraufbereitung eingesetzt. Chlorit konnte im Rahmen der analytischen Nachweisgrenze der verwendeten ionenchromatographischen Methode (1 mg/l) in keiner der Proben nachgewiesen werden. Die Chloratkonzentrationen im Beckenwasser der Bäder liegen im Gegensatz hierzu teilweise sehr hoch und erreichen Werte von bis zu 40 mg/l. Hohe Werte treten insbesondere in Schwimmbädern auf, deren Wasser mit Hypochloritlösung desinfiziert wird. Einige Bäder wurden daneben auf ihren Bromatgehalt untersucht und es wurde eine stichprobenartige Kontrolle der Hypochloritvorratslösungen in 9 Bädern vorgenommen. Es ergab sich eine Chloratkonzentration von 15 bis 44,5 g/l in der Vorratslösung, die Bromatkonzentration betrug bis zu 1,2 g/l. In Bädern, deren Wasser mit Chlorgas behandelt wird, ist die Belastung mit Chlorat im Durchschnitt sehr viel niedriger. Die Verwendung von Ozon zur Wasseraufbereitung hat nach unseren bisherigen Untersuchungen im Rahmen der Meßgenauigkeit keinen wesentliche Einfluß auf die Chloratkonzentration. Chlorat beeinflußt die Messung der Hygiene-Hilfsparameter (z. B. ph-Wert und Redoxpotential) nicht, es stört auch nicht die Bestimmung von freiem oder gebundenem Chlor. Die gesundheitliche Bedeutung der teilweise sehr hohen Werte kann zum jetzigen Zeitpunkt nicht eindeutig eingeschätzt werden. Unsere Untersuchungen zeigen, daß Chlorat weder cytotoxische (Neutralrot-Assay), noch schleimhautreizende Wirksamkeit (HET-CAM-Assay) besitzt. Es ist jedoch bekannt, daß Chlorat ebenso wie Chlorit Wirkungen auf das blutbildende System zeigt. Für Chlorit wurde in der Trinkwasserverordnung ein Grenzwert von 0,2 mg/l (als Desinfektionsnebenprodukt bei der Verwendung von Chlordioxid) festgelegt. Es wird empfohlen, Maßnahmen mit dem Ziel zu ergreifen, die Belastug von Schwimmbadwasser mit Chlorat und Bromat zu minimieren.
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 22.03.2021